2023
DOI: 10.1002/pssa.202200858
|View full text |Cite
|
Sign up to set email alerts
|

CdTe/CdS Core–Shell Quantum Dots: Synthesis and Applications as a Heavy Metal Ion's Fluorescence Sensor and Photocatalyst for Photodegradation of Organic Dyes

Abstract: Herein, a simple method for the growth of the CdS shell around CdTe QDs and the formation of the CdTe/CdS core–shell structure is proposed. The synthesized QDs are characterized using Raman, Fourier‐transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), transmission electron microscopy (TEM), photoluminescence (PL), and UV–vis analyses. XRD patterns confirm the formation of a core–shell‐type structure and particle sizes, lattice strain (ε), and displacement density (δ) are calculated using Williamson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The large-area SEM image (Figure S1) and the corresponding inset show that the UQSN-115 surface has no apparent pore size, probably originating from the further hydrolyzed and rapidly reorganized −Si–O- bonds on the surface of DMSN-MPA . This may be attributed to the alkaline growth environment of QDs at high temperatures and pressures that promotes recondensation of silicates. ,, The black dots with a size of approximately 3 nm in the TEM image (Figure c) directly evidence the successful growth of CdTe QDs in the DMSN-template, and the lattice of CdTe QDs is around 0.3 nm (inset in Figure d). , Meanwhile, the high-resolution TEM (HRTEM) image of UQSN-115 is shown in Figure S2. As indicated in the TEM-high-angle annular dark field (TEM-HAADF) image (Figure e) of UQSN-115, the numerous bright spots indicate the high loading and homogeneous distribution of CdTe in the silica matrix, which is further supported by the energy-dispersive X-ray spectroscopy (EDS) elemental mappings (Figure f).…”
Section: Resultsmentioning
confidence: 95%
“…The large-area SEM image (Figure S1) and the corresponding inset show that the UQSN-115 surface has no apparent pore size, probably originating from the further hydrolyzed and rapidly reorganized −Si–O- bonds on the surface of DMSN-MPA . This may be attributed to the alkaline growth environment of QDs at high temperatures and pressures that promotes recondensation of silicates. ,, The black dots with a size of approximately 3 nm in the TEM image (Figure c) directly evidence the successful growth of CdTe QDs in the DMSN-template, and the lattice of CdTe QDs is around 0.3 nm (inset in Figure d). , Meanwhile, the high-resolution TEM (HRTEM) image of UQSN-115 is shown in Figure S2. As indicated in the TEM-high-angle annular dark field (TEM-HAADF) image (Figure e) of UQSN-115, the numerous bright spots indicate the high loading and homogeneous distribution of CdTe in the silica matrix, which is further supported by the energy-dispersive X-ray spectroscopy (EDS) elemental mappings (Figure f).…”
Section: Resultsmentioning
confidence: 95%
“…It was also demonstrated that Cu 2+ ions showed high affinity towards the sulfide bond present in DDTC and 3-MPA, quenching the fluorescence of CdSe/CdS QD and CdSe QD, respectively. 109,132,148 Doping other metal ions enhances the QY of QDs. 112,149 Uppa et al 150 enhanced the fluorescence of cysteamine capped-CdS quantum dots using the silver ion (Ag + @Cys-CdS QDs), which was quenched by the Hg 2+ ion.…”
Section: Fluorescence Quenching By Analyte Through Direct Attachment ...mentioning
confidence: 99%
“…It was also demonstrated that Cu 2+ ions showed high affinity towards the sulfide bond present in DDTC and 3-MPA, quenching the fluorescence of CdSe/CdS QD and CdSe QD, respectively. 109,132,148…”
Section: Turn-off Strategiesmentioning
confidence: 99%
“…Furthermore, they demonstrated improved photocatalytic capabilities in comparison to bare CdTe CQDs; the CdTe/CdS core-shell CQDs degraded the MO dye by 88.2% when exposed to UV light. 335 The degradation efficiencies of the CQD-based systems, along with the types of dyes and pollutants, are listed in Table 11.…”
mentioning
confidence: 99%